ACP-EU Trade Issues in the Agricultural and Fisheries Sectors: 2009 Compendium - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
The present publication is a compendium of briefings published on the CTA Agritrade web site in 2008.The issues are addressed in a factual and non-partisan manner.